Analysis of Trend and Variability of Climate of Hawassa Based on Surface Observations - Alandu, Kefiyalew Ayele (International Journal of Climate Research, 2020)
Precipitation and temperature are the main determinants of climate change and variability of one’s area. Their change can be disruptive to the normal hydrological processes which plays an important role in agricultural and non-agricultural operations activities. This study is to determine climatology, trends, onset and retreat of rainy seasons and variation in temperature and precipitation by statistical and Mann Kendall test methods at Hawassa station for the period of 1973-2018. The increasing trend of minimum and maximum temperature were detected to be 0.05 and 0.04°C with high coefficient of determination (R2 = 0.63 and 0.66), respectively. Besides, annual rainfall showed a coefficient of variation 15.2% with mean and standard deviation 965.3mm and 146.5, respectively. Seasonally, Belg season showed higher variability with statistical significant an increasing trend. And also the mean onset Belg season was identified as in the 1st decade of March and cessation date was in the 2nd decade of May, and Kiremt season mean onset was after 1st decade of June and cessation in the 2nd decade of September. The observed warming temperature and fluctuation of rainfall are impacts of global climate change during the last decades in the area.